The impact of V-flow on preoperative diagnosis of thyroid tumors: individually and as part of multimodal sonographic imaging - Brandenstein, Moritz Konstantin; Zhang, Liang; Scharf, Gregor; Thurn, Sylvia; Hornung, Matthias; Menhart, Karin; Meiler, Stefanie; Stroszczynski, Christian; Jung, Ernst Michael (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
V-flow is a dynamic ultrasound technique that visualizes perfusion patterns by displaying dynamic arrows that change in response to the flow of erythrocytes. Furthermore, it provides quantitative values for the maximum and mean velocity of blood flow as well as a percentage value for turbulence. The aim was to enhance the preoperative diagnostic accuracy of thyroid lesions by combining V-flow with established ultrasound modes.B-mode, CCDS, elastography, CEUS, and V-flow were performed on 101 patients. After the ultrasound examination, every nodule was confirmed as benign or malignant via histopathology. The Kruskal–Wallis test, ROC curve, and binary logistic regression were used for the statistical analysis.93 benign regressive thyroid nodules and 8 carcinomas were included in this study. The average mean velocity value for benign lesions was measured at 19.5 cm/s and at 10.7 cm/s for malignant lesions (p = 0.039). The average turbulence percentage was 26.1% for benign nodules and 46.7% for carcinomas (p = 0.016). Carcinomas exhibited a slower and more turbulent perfusion pattern compared to benign tumors. A V-flow-centered system achieves a sensitivity of 100.0% and a specificity of 84.9% in predicting malignancy. This system could have reduced the number of unnecessary thyroid surgeries for benign lesions in our patient group by 70%.The capillary perfusion of thyroid nodules represents a significant indicator of its status. By analyzing the velocity and turbulence level of microvascular blood flow, V-flow offers promising prospects for accurately distinguishing between benign and malignant thyroid lesions. When integrated into a comprehensive multimodal sonographic imaging approach, V-flow further enhances diagnostic accuracy.
Keywords: thyroid; V-flow; hemodynamics/flow dynamics; multimdodal sonographic imaging; adenocarcinoma; microvascularization